2017
DOI: 10.1103/physrevb.96.184203
|View full text |Cite
|
Sign up to set email alerts
|

Förster-type triplet-polaron quenching in disordered organic semiconductors

Abstract: Triplet-polaron quenching (TPQ) is a major cause of the efficiency loss at large current densities in phosphorescent organic light-emitting diodes. The nature of the interaction process is presently not well understood. In this paper, we study TPQ due to Förster-type triplet-polaron interactions in energetically disordered organic semiconductors with a Gaussian polaron density of states. A continuum theory, which neglects the spatial inhomogeneity and energetic disorder, is from a kinetic Monte Carlo approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…This view is also supported by kinetic Monte Carlo simulations, which found that holes in a CBP:Ir(ppy) 3 device spend >95% of the time on Ir(ppy) 3 molecules ( 42 ). The typical Förster radius for energy transfer from a phosphorescent emitter to its cation has been estimated at 2 to 3 nm ( 40 ), similar to the hole distribution width extracted here. If Förster-type EPQ is active here, then a narrower charge distribution could be consistent with our results.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This view is also supported by kinetic Monte Carlo simulations, which found that holes in a CBP:Ir(ppy) 3 device spend >95% of the time on Ir(ppy) 3 molecules ( 42 ). The typical Förster radius for energy transfer from a phosphorescent emitter to its cation has been estimated at 2 to 3 nm ( 40 ), similar to the hole distribution width extracted here. If Förster-type EPQ is active here, then a narrower charge distribution could be consistent with our results.…”
Section: Resultssupporting
confidence: 76%
“…It is also possible that the distributed charge density predicted by our model is an artifact of its simplified description of EPQ. EPQ may occur either by nearest-neighbor interactions or by long-range Förster transfer (6,40), which requires overlap between the emission spectrum of the emitter and the absorption spectrum of the cation. Here, the holes responsible for quenching most likely reside on Ir(ppy) 3 molecules, as the Ir(ppy) 3 + cation absorbs near 600 nm (41) and Ir(ppy) 3 has a shallower highest occupied molecular orbital energy than CBP, TPBi, and 4,4′,4″-tris(N-carbazolyl)triphenylamine (TCTA), leading to hole trapping.…”
Section: Eqe Plmentioning
confidence: 99%
“…Similarly, the loss due to TPQ is expressed using the expression dT /dt = −k TPQ nT , with n the polaron volume density. From KMC simulations, we have shown that these descriptions can indeed provide a proper description of the local rate, but not under all conditions [12][13][14]. For Förster-type TTA, k TT is not a constant but increases at high triplet densities [12].…”
Section: Introductionmentioning
confidence: 92%
“…Note that as an approximation polaron quenching as well as annihilation processes are modeled purely locally. Alternatively, these processes can also be modeled using long-range Förster type interactions [10,11].…”
Section: Modelmentioning
confidence: 99%